Sustainable production of Zacapa melon (Cucumis melo L.) with beneficial microorganisms - Miranda-Ramírez, José Mario; Perales-Segovia, Catarino; González-Gaona, Ernesto; Perales-Aguilar, Lucila (Ecosistemas y Recursos Agropecuarios, 2025)
In Mexico, there is very little research on beneficial microorganisms used as biofertilizers for melon cultivation, which implies insufficient use by farmers. The effect of beneficial microorganisms in open-air cultivation of Harper melon [Zacapa] was evaluated in relation to growth and yield. The experiment was carried out at Crucero de la Ruana, Buenavista municipality, Michoacán, Mexico. A completely randomized experimental design was used, with thirteen treatments and ten repetitions. The experimental unit was a melon plant. The treatments evaluated were five beneficial microorganisms Pseudomonas fluorensces, Bacillus subtilis, Azospirillum brasilense, Trichoderma harzianum and Glomus fasciculatum (syn Rhizophagus fasciculatus), seven mixtures of these, compared with a control without application and ten variables were measured: Main Stem Diameter, Yield, Fruit Weight, among other. Data collection was done 70 days after transplant. The best results for the Main Stem Diameter variable were presented in the mixtures Trichoderma harzianum + Glomus fasciculatum and Azospirillum brasilense + Glomus fasciculatum with 10.60 and 10.51 mm respectively. In the Yield, the highest values favored Basillus subtilis; Trichoderma harzianum and the mixture Bacillus subtilis +Azospirillum brasilense with 31.78, 29.49 and 27.79 t ha-1 or 1 765.54, 1 638.43 and 1 543.70 Bruce boxes ha-1, corresponding. The biggest fruit size was achieved with Glomus fasciculatum, reason why the use of this microorganism is justified.